2013
DOI: 10.2304/ciec.2013.14.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Discourses of Professionalism in Family Day Care

Abstract: Family day care in Australia is currently undergoing rapid 'professionalisation' within a national reform agenda that seeks to raise and standardise early childhood service quality. Included within this reform is a requirement that all family day care workers obtain formal qualifications and that workers are referred to as 'educators' rather than 'carers'. This study drew on focus groups and interviews with family day care workers, management, government and industry representatives collected as part of a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The care component of early childhood work is often positioned by wider society as akin to mothering, and this positioning 'has been viewed as the major stumbling block in the road towards raising both "quality" and "status"' (O'Connell, 2011, p. 781). In Australia a similar positioning is seen in the arguments around the caring work associated with family day care (Cook, Davis, Williamson, Harrison & Sims, 2013). This link with mothering provides a motivation to exclude care work from early childhood, as it is an impediment to professionalisation.…”
Section: Discussionmentioning
confidence: 81%
“…The care component of early childhood work is often positioned by wider society as akin to mothering, and this positioning 'has been viewed as the major stumbling block in the road towards raising both "quality" and "status"' (O'Connell, 2011, p. 781). In Australia a similar positioning is seen in the arguments around the caring work associated with family day care (Cook, Davis, Williamson, Harrison & Sims, 2013). This link with mothering provides a motivation to exclude care work from early childhood, as it is an impediment to professionalisation.…”
Section: Discussionmentioning
confidence: 81%
“…Our analysis has shown that in recent history, the most successful strategy for revaluing women’s caring work in Australia has been to align ECEC workforce problems with the facets of neoliberal thinking that value investments in the early education of the next generation of workers (Osgood, 2006). However, the deployment of ‘professionalisation’ as a strategy in this context remains contentious, as it is argued that this jettisons claims for women’s work to be recognised on its own terms, and instead ties ECEC work into masculine conceptions of quality assurance, measurement and standardisation (Boyd, 2013; Cook et al, 2013; Moss, 2006; Osgood, 2006). In any case, current approaches that serve either to align with neoliberal future-worker-investment discourses or enshrine ECEC as women’s work will not achieve a re-imagination of the value of care, as they do not address the ‘excuses’ (Tronto, 2013) afforded to middle-class parents that legitimate their abdication of their responsibilities for care on the basis of their labour market engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Across a range of developed countries, the ECEC sector has moved to reconstruct its practice as requiring specialised knowledge and skills (Harwood, et al, 2012; Taggart, 2011). This reconstruction positions ECEC work as of educational benefit to children and, as such, reframes ECEC workers as educators (Cook et al, 2013; Osgood, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, being a ‘caregiver’ potentially constrains the possibilities of the role and identity of ECEs as qualified and knowledgeable education professionals. On the other hand, moves in Australia to ‘professionalise’ ECE by adopting the term ‘educator’ rather than ‘carer’ in Family Day Care contexts, for example, have been challenged (Cook et al, 2013). This example highlights Broström’s (2006) reflection on the importance of the way the concept of care is defined.…”
Section: The Practice Architectures Of Ecementioning
confidence: 99%